Business, society and politics multinationals in emerging markets - Elg, Ulf; Hadjikhani, Amjad; Ghauri, Pervez N., 1948- (International business and management series ;, 2012)
This volume looks at interaction between business firms and socio-political actors in emerging markets - and how this relationship can be managed - and deals with the interconnection between the socio-political organizations in emerging markets and MNCs. Inferring to different business perspectives, the volume includes papers studying firms' strategic actions towards socio-political organizations, i.e. the interplay with socio-political actors and how this affects firms' competitive advantage in a particular market. The book discusses this in relation to a number of critical strategic areas such as brand building, market orientation and CSR. It also offers a number of practical illustrations from empirical studies from different markets. In this volume different authors contribute chapters focusing on diverse empirical and theoretical aspects covering the impact of socio-political environments on the success of international firms.